The suffering of women living in an informal settlement in São Paulo, Brazil: a challenge to the work of Primary Health Care - Aline Messias Mota; Rubens Bedrikow (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
Among the social effects of the COVID-19 pandemic, increased poverty, unemployment, and social inequality in Brazil have led to worsening health problems, especially in the poorest citizens. The purpose of this research was to discuss the potentialities and limitations of the work process in primary health care based on the Family Health Strategy. In order to do so, we conducted semi-structured interviews with four women living in an informal settlement in the interior of the state of São Paulo, Brazil, between January and February 2020. We found that the women experienced suffering in relation to issues such as housing precariousness, transience, social isolation, and silencing. The way in which primary health care is organized and professionals' work processes make it difficult for this population to access health services and for professionals to perceive their suffering. The findings of this research point to the need to reevaluate and improve the Family Health Strategy.